Utilization of the Shensheng-Piwen changed medicinal powder extracts combines metal-organic frameworks as an antibacterial agent - Jin, Haiqun; Zhang, Xiujun; Ma, Xiaoqing; Meng, Xin; Lin, Zhenguang; Li, Xiaoyuan; Hu, Guojie; Chen, Yao (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Widespread opportunistic pathogens pose a serious threat to global health, particularly in susceptible hospital populations. The escalating crisis of antibiotic resistance highlights the urgent need for novel antibacterial agents and alternative treatment approaches. Traditional Chinese Medicine (TCM) and its compounds have deep roots in the treatment of infectious diseases. It has a variety of active ingredients and multi-target properties, opening up new avenues for the discovery and development of antimicrobial drugs. Methods This study focuses on assessing the efficacy of the Shensheng-Piwen changed medicinal powder (SPC) extracts against opportunistic pathogen infections by broth microdilution and agar disc diffusion methods. Additionally, biofilm inhibition and eradication assays were performed to evaluate the antibiofilm effects of SPC extracts. Results Metabolite profiles were analyzed by LC-MS. Furthermore, the potential synergistic effect between SPC and Metal-Organic Framework (MOF) was investigated by bacterial growth curve analysis. The results indicated that the SPC extracts exhibited antibacterial activity against S. aureus, with a minimum inhibitory concentration (MIC) of 7.8 mg/mL (crude drug concentration). Notably, at 1/2 MIC, the SPC extracts significantly inhibited biofilm formation, with over 80% inhibition, which was critical in tackling chronic and hospital-acquired infections. Metabolomic analysis of S. aureus revealed that SPC extracts induced a notable reduction in the levels of various metabolites, including L-proline, L-asparagine. This suggested that the SPC extracts could interfere with the metabolism of S. aureus. Meanwhile, the growth curve experiment proved that SPC extracts and MOFs had a synergistic antibacterial effect. Discussion In conclusion, the present study highlights the potential of SPC extracts as a novel antibacterial agent against S. aureus infections, with promising biofilm inhibition properties. The observed synergistic effect between SPC extracts and MOFs further supports the exploration of this combination as an alternative treatment approach.